Migration and Globalization: Challenges and Perspectives for the Research Infrastructure - Martin Kahanec; Klaus F. Zimmermann (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2008)
International migration of people is a momentous and complex phenomenon. Research on its causes and consequences, requires sufficient data. While some datasets are available, the nature of migration complicates their scientific use. Virtually no existing dataset captures international migration trajectories. To alleviate these difficulties, we suggest: (i) the international coordination of data collection methodologies and standardization of immigrant identifiers; (ii) a longitudinal approach to data collection; (iii) the inclusion of adequate information about relevant characteristics of migrants, including retrospective information, in surveys; (iv) minimal anonymization; (v) immigrant boosters in existing surveys; (vi) the use of modern technologies and facilitation of data service centers; and (vii) making data access a priority of data collection.
Keywords: J15; J18; J61; J68; 330; migration; immigrants; data collection; data access; data infrastructure